PENGARUH KARAKTERISTIK PEKERJAAN DAN STRES KERJA TERHADAP KINERJA KARYAWAN - Devilia, Wanda; Norisanti, Nor; Z, Faizal Mulia (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
The objectives of this study are 1) To determine the job characteristics, job stress and employee performance at PT Pegadaian Sukabumi.2) To determine whether job characteristics affect employee performance at PT. Pegadaian Sukabumi. 3) The research method used by researchers is quantitative research with a descriptive approach. The results of this study indicate that there is a positive and significant influence between job characteristics on employee performance. And there is a positive and significant influence between Job Stress on Employee Performance.